RELATIONSHIP OF OHA’S TREATMENT RATIONALITY WITH THERAPY TARGETS ACHIEVEMENT IN TYPE II DIABETES MELLITUS PATIENTS - Rizky, Wardhiana Agung; Annisaa, Eva; Dini, Intan Rahmania Eka (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Diabetes mellitus (DM) is the most common condition in Central Java. Irrational use of drugs can cause various problems, including increased disease morbidity and mortality rates, wasted health costs, and the emergence of undesirable effects. Therefore, this study was necessary to assess the rationality of the treatment. The aim was to describe the rationality of OHAs treatment and to achieve therapy targets, and to understand the relationship between OHA treatment rationality and therapy target achievement in patients with type 2 diabetes mellitus at primary health care in Wirosari District, Grobogan Regency. An analytical observational study used a cross-sectional design, purposive sampling, and chi-square test to establish relationships between variables. The rationale for treating OHAs in patients with type 2 diabetes mellitus at primary health care in Wirosari District, Grobogan Regency, is 47.67% rational and 52.33% irrational. Among the samples, 26.7% reached the therapeutic target, whereas 73.3% did not. The rationality of treating OHAs and achieving therapeutic targets was interconnected (p=0.014). Keywords: HbA1C, rational treatment, therapeutic target, type 2 diabetes mellitus